After ten years of follow-up, no difference between supportive care plus immunosuppression and supportive care alone in IgA nephropathy - Rauen, Thomas; Wied, Stephanie; Fitzner, Christina; Eitner, Frank; Sommerer, Claudia; Zeier, Martin; Otte, Britta; Panzer, Ulf; Budde, Klemens; Benck, Urs; Mertens, Peter R.; Kuhlmann, Uwe; et al. (Kidney International, 2020)
The randomized, controlled STOP-IgAN trial in patients with IgA nephropathy (IgAN) and substantial proteinuria showed no benefit of immunosuppression added on top of supportive care on renal function over three years. As a follow-up we evaluated renal outcomes in patients over a follow-up of up to ten years in terms of serum creatinine, proteinuria, end-stage kidney disease (ESKD), and death. The adapted primary endpoint was the time to first occurrence of a composite of death, ESKD, or a decline of over 40% in the estimated glomerular filtration rate (eGFR) compared to baseline at randomization into STOP-IgAN. Data were analyzed by Cox-regression models. Follow-up data were available for 149 participants, representing 92% of the patients originally randomized. Median follow-up was 7.4 years (inter quartile range 5.7 to 8.3 years). The primary endpoint was reached in 36 of 72 patients randomized to supportive care and 35 of 77 patients randomized to additional immunosuppression (hazard ratio 1.20; 95% confidence interval 0.75 to 1.92). ESKD occurred in 17 of the patients with supportive care and in 20 of the patients with additional immunosuppression. Additionally, the rates of eGFR loss over 40% and annual eGFR loss did not differ between groups. Two patients died with supportive care and three with additional immunosuppression. Thus, within the limitations of a retrospective study, over a follow-up of up to ten years, and using an adapted primary endpoint, we failed to detect differences in key clinical outcomes in IgAN patients randomized to receive added immunosuppression on top of supportive care versus supportive care alone.
CRIS-Team Scopus Importer:2020-09-11
Keywords: IgA nephropathy; IgAN; immunosuppression; long term; STOP-IgAN